Seasonal influence on biochemical profile and serum protein electrophoresis for Boa constrictor amarali in captivity - Silva, LFN [UNESP]; Costa, Ciniro [UNESP]; Ramos, PRR [UNESP]; Takahira, RK [UNESP] (Instituto Internacional de Ecologia, 2011)
As serpentes, como outros répteis, são animais ectotérmicos e dependem exclusivamente do meio para a manutenção de seus processos fisiológicos, bioquímicos e imunológicos. Desta forma, alterações nos valores bioquímicos podem ser esperadas considerando-se a influência sazonal. Foram utilizadas vinte e duas Boa constrictor amarali adultas mantidas em cativeiro. A coleta de sangue foi realizada em duas estações diferentes: inverno (julho 2004) e verão (Janeiro 2005), para a realização dos exames: ácido úrico, aspartato aminotransferase (AST), glicose, colesterol, proteína total e eletroforese da proteína sérica. As médias dos exames bioquímicos obtidos no verão e inverno, respectivamente, foram: 6.3 ± 3.4 e 11.3 ± 6.2 mg/dL para ácido úrico; 28.7 ± 12.4 e 20.7 ± 16.2 UI/L para AST; 26.3 ± 17 e 17.4 ± 6.8 mg/dL para glicose; 67.3 ± 30.2 e 69.7 ± 38.5 mg/dL para colesterol; e 5.9 ± 1.6 e 5.9 ± 1.4 g/dL para proteína total. Os resultados da eletroforese no verão e inverno, respectivamente, foram: 1.9 ± 0.7 e 2.4 ± 0.6 g/dL para albumina; 0.7 ± 0.2 e 0.5 ± 0.2 g/dL para α globulina; 1.5 ± 0.5 e 1.7 ± 0.6 g/dL β globulina; e 1.8 ± 0.5 e 1.5 ± 0.5 g/dL para g globulina. No verão foi observado aumento significativo da AST (p < 0,05) e diminuição significativa do ácido úrico (p < 0,05). Na eletroforese de proteína sérica, houve um aumento significativo da fração a globulina (p < 0,05) na mesma estação. Para as outras variáveis não foram obtidas diferenças significativas entre as estações. de acordo com os resultados, é importante considerar o período do ano na interpretação de alguns exames bioquímicos desses animais.

Similarly to other reptiles, snakes are ectothermic animals and depend exclusively on the environment for the maintenance of their physiological, biochemical and immunological processes. Thus, changes in biochemical values can be expected due to seasonal influence. Twenty-two adult specimens of Boa constrictor amarali kept in captivity were used. Blood collections were done in two different seasons: winter (July 2004) and summer (January 2005) for the following assays: uric acid, aspartate aminotransferase (AST), glucose, cholesterol, total protein, and serum protein electrophoresis. The mean biochemical results found in summer and winter, respectively, were: 6.3 ± 3.4 and 11.3 ± 6.2 mg/dL for uric acid; 28.7 ± 12.4 and 20.7 ± 16.2 UI/L for AST; 26.3 ± 17 and 17.4 ± 6.8 mg/dL for glucose; 67.3 ± 30.2 and 69.7 ± 38.5 mg/dL for cholesterol; and 5.9 ± 1.6 and 5.9 ± 1.4 g/dL for total protein. Results regarding electrophoresis in summer and winter, respectively, were: 1.9 ± 0.7 and 2.4 ± 0.6 g/dL for albumin; 0.7 ± 0.2 and 0.5 ± 0.2 g/dL for α-globulin; 1.5 ± 0.5 and 1.7 ± 0.6 g/dL for β-globulin; and 1.8 ± 0.5 and 1.5 ± 0.5 g/dL for g-globulin. In the summer, there was a significant increase in AST and a decrease in uric acid (p < 0.05). Serum protein electrophoresis showed a significant increase in α-globulin fraction (p < 0.05) in the same season. There were not significant differences between seasons for the remaining variables. Based on these results, the period of the year must be considered in the interpretation of some biochemical values for these animals.
Influência sazonal sobre o perfil bioquímico e a eletroforese de proteínas séricas de Boa constrictor amarali criada em cativeiro
Keywords: perfil bioquímico; serpente; Boa constrictor amarali; eletroforese; influência sazonal; biochemical profile; snake; Boa constrictor amarali; electrophoresis; seasonal influence